Serapan Karbon Pada Empat Jenis Mangrove (Rhizophora apiculate, Avicennia alba, Bruguiera parviflora, Avicennia alba, Xylocarpus granatum) Di Desa Selotong - Lia Annisa; Mufti Sudibyo (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
Karang Gading Wildlife Reserve East Langkat is a mangrove protection area that has great potential for carbon sequestration. This research aims to determine the amount of biomass content, level of carbon uptake and comparison of carbon dioxide uptake in four types of mangrove leaves (Rhizophora apiculata, Bruguiera parviflora, Avicenia alba, Xylocarpus granatum) in Selotong Village. Sampling was carried out at three stations determined by purposive sampling, each with three replicate samples. Mangrove leaves are analyzed in the laboratory by measuring the water content and ash content using the Loi (loss on ignation) method. The results showed that carbon uptake materials from highest to lowest respectively was Rhizophora apiculata 28.4 ± 0.6 (g/g-dry), Bruguiera parviflora 27.6 ± 0.3 (g/g-dry), Xylocarpus granatum 26.3 ± 2.3 (g/g-dry) and Avicennia alba 25. .7 ± 1.8 (g/g-dry). Statistical analysis of the length, width and thickness of the leaves of the 4 types of mangrove leaves showed no difference in CO2 absorption capacity.